SMALL: soluções computacionais em mobilidade urbana para auxiliar na consolidação de cidades inteligentes - Santos, Alef Menezes dos (2021)
The United Nations (UN) estimates that there will be an increase in the world population and, consequently, the growth of population living in urban areas until 2050, reaching approximately 70% of the world population. In Brazil, the Brazilian Institute of Geography and Statistics (IBGE) revealed population growth and an increase in the rate of urbanization, from 26.4% between 1940 and 1950 to 84.2% between 2010 and 2020. The Institute of Applied Economic Research (IPEA) states that approximately 85% of the Brazilian population was concentrated in urban centers in 2016. The growth of the population and urban activities has led to the emergence of problems in urban systems, such as congestion, increased traffic, reduced well-being, overcrowding, difficulty in planning routes, security, among others, thus affecting Urban Mobility (UM). Based on the scenario presented, Brazilian government developed the Law Number 14,000/2020. It defines the guidelines of the national UM policy on the elaboration and approval of the Urban Mobility Plan (UMP) by the municipalities. However, the problems of UM can no longer be solved effectively using only traditional solutions, initiating the creation of new approaches, such as Intelligent Transport Systems (ITS). ITS are advanced applications of Information and Communication Technologies (ICT), used in the field of road transport, including infrastructure, vehicles and users, traffic and mobility management, as well as for interfaces with other modes of transport. Therefore, in order to assist managers in the identification of computational ITS solutions, this work presents a Systematic Mapping of Literature (SML) with 225 articles with some types of ITS. In the SML, 11 sub-axis classifications of UM are created, namely: Accessibility, Road Conditions, Environmental Disasters, Parking, Multimodal, Guidance/Recommendation, Security, Essential Services, Innovative Solutions, Sustainability, and Traffic and Congestion. This work also presents the proposal for the Smart Mobility for ALL (SMALL) Guide, based on the SLM. It presents 30 different issues addressed in 46 scientific articles of the “Application” type, which are divided into 11 sub-axes. The SMALL guide indicates the negative implications that each of the 30 problems can cause and provides brief descriptions of what each solution offers as a means of mitigating or solving them. Finally, an interview is presented with the UM manager of one of the capitals of the Brazilian states. This interview aimed to identify the current technological situation in that capital and evaluated the SMALL guide.